The Influence of Non-Financial Compensation, Training, Promotion and Mutation on Employee Satisfaction and Performance at BPJS Health in Bali - Ni Made Noviani Saputri (Global Researcher Network, 2022)
The results of PT. Askes (Persero)'s internal customer satisfaction survey showed that the level of internal customer satisfaction for the Bali Nusra Region was 69.25%. This meant that it had not reached the management target set at 85%. Efforts that can be made to achieve customer satisfaction are to improve employee performance. Therefore, the purpose of this study is to determine and analyze the effect of non-financial compensation, training, promotion and mutation on employee job satisfaction, and to find out and analyze the effect of non-financial compensation, training, promotion and mutation, job satisfaction on employee performance. The population in this research is 140 permanent employees of BPJS Health in Bali. The selection of respondents in each district used a random sampling method and the number of samples used was 58 people. The analysis technique uses the Partial Least Square (PLS) test with SmartPLS 3.0 M3 program tools. The analysis shows that non-financial compensation, training, promotions and mutations have a positive and significant effect on employee job satisfaction. The results show non-financial compensation, training, promotion and mutation, as well as job satisfaction have a positive and significant effect on employee performance. The analysis also shows job satisfaction has a positive and significant effect on employee performance. This shows that the higher the job satisfaction of employees, the higher the performance that will be generated by BPJS Health employees in Bali Province.